Doublon Production in Correlated Materials by Multiple Ion Impacts. Issue 4 (26th February 2022) - Borkowski, Lotte; Schlünzen, Niclas; Joost, Jan-Philip; Reiser, Franziska; Bonitz, Michael
Abstract : Recently, it was demonstrated that ions impacting a correlated finite graphene‐type honeycomb cluster can excite strong nonequilibrium states. In particular, this can lead to an enhanced population of bound pairs of electrons with opposite spin—doublons—where the doublon number can be increased further via multiple ion impacts. These predictions were made based on nonequilibrium Green functions (NEGF) simulations allowing for a time‐dependent non‐perturbative study of the energy loss of charged particles penetrating a strongly correlated system. Herein, these simulations are extended to larger clusters and longer simulation times, utilizing the recently developed G1–G2 scheme, which allows for a dramatic speedup of NEGF simulations. Furthermore, the dependence of the energy and doublon number on the time interval between ion impacts and on the impact point is investigated. Abstract : The formation of doublons (bound electron pairs) in correlated graphene‐type nanostructures following proton impacts is studied. The authors focus on the dependence of the energy and doublon number on the time interval between ion impacts and on the impact point. The simulations are done utilizing the recently developed G1–G2 scheme.